From Textuality to Universality: The Evolution of Ḥirābah Crimes in Islamic Jurisprudence - Moh Khasan (Al-Jami'ah Research Centre, 2021)
The issue of the escalation of crime, which is increasingly varied and is getting heavier, is becoming a global concern. The development and progress of the world seems to have contributed to changes in the type and quality of crime, not only in the form and method, but also in the damage it causes. Crime trends increasingly point to collective crimes, systematic crimes, and crimes with extensive and massive excess damage. This article intends to criticize the systematic change (evolution) that has occurred in the concept of ḥirābah crime in Islamic law from a classical to contemporary perspective. The qualitative analysis of this article is focused on three fundamental issues, namely; ḥirābah interpretation, ḥirābah liability, and ḥirābah punishment. The author reveals in the conclusion that; first, based on its elements and characteristics, the definition of ḥirābah can be expanded to include new types of crimes such as; terrorism, rape, and drug trafficking and smuggling. Second, it is necessary to reconstruct the ḥirābah responsibility theory into a formulation that considers the principle of legal certainty and the principle of equality before the law. The reconstruction model, among others, is the affirmation that all people who involve themselves in the crime are perpetrators of ḥirābah (with an ishtirāk approach). Likewise, reconstruction efforts are needed to enforce equality of accountability between male and female actors. Third, as a serious crime, ḥirābah deserves a severe punishment and has a strong deterrent effect, as offered by Islamic law. However, the opportunity to give dispensation to the punishment will always be open if the perpetrator can prove his seriousness in repenting.[Eskalasi kriminalitas yang semakin beragam dan berat telah menjadi perhatian global saat ini. Pembangunan dan kemajuan dunia berkontribusi pada perubahan pola dan tingkat kriminalitas, tidak hanya bentuk dan cara, tetapi juga akibat yang ditimbulkan. Trend kriminalitas berkembang mulai dari yang berkelompok, sistematis, hingga menyebabkan kerusakan yang masif dan lama. Tulisan ini mengkritisi perubahan sistematis pada konsep jarimah ḥirābah dalam hukum Islam dari pendekatan klasik hingga kontemporer. Analisis kualitatif dalam tulisan ini fokus pada tiga hal mendasar yaitu pemaknaan, pertanggungjawaban dan hukuman ḥirābah. Kesimpulan pertama tulisan ini adalah bahwa definisi ḥirābah berdasarkan unsur dan karakteristiknya dapat diperluas mencakup terorisme, pemerkosaan, perdagangan dan penyelundupan obat-obat terlarang. Kedua, perlu rekonstruksi teori pertanggungjawaban ḥirābah menuju formulasi yang mempertimbangkan kepastian hukum dan kesetaraan hak dimuka hukum. Ketiga, sebagai kejahatan serius, ḥirābah pantas mendapat hukuman berat dan mempunyai efek pencegahan yang kuat seperti halnya dalam hukum Islam. Meski demikian, ada peluang dispensasi hukuman jika pelaku dapat menunjukkan kesungguhan untuk bertobat.]